Perancangan Videografi Sebagai Media Promosi Batik Khas Subang Yang Diproduksi Oleh Batik Ganasan - Ogi Sugianto; Nichi Hana Karlina; Sophia Purbasari (Universitas Informatika dan Bisnis Indonesia, 2019)
Since batik was established by UNESCOas a Masterpece of the Oral and Intangible Haritage of Humanity Culture since October 2009, the development of batik in Indonesia developed rapidly, many regions in Indonesia possessed and developed batik in accordance with regional identity, including in Subang Regency which has developed and has emerged a variety of typical Batik Subang industry. One of the famous batik industries in Subang is Batik Ganasan. In Ganasan Batik, batik cloth is made with diverse motifs and is full of natural wealth and traditions in Subang Regency, such as pineapple motifs, sisingaan and ancient vessels. This Final Project Design Report on Subang Batik has the formulation of the problem regarding effective and efficient promotional media for the work on typical Batik Subang that produces Batik Ganasan. The purpose of the design of this Final Project is to promote the unique batik of Subang through videography media and the target of designing this promotional media is the early adultage is actively using social media.This study uses qualitative methods, with primary data collection techniques in the form of interviews, observation and literature study, and secondary data using a questionnaire as a data collection medium. Based on the data analysis, it was concluded that the Batik Ganasan industry had made an effort to promote the typical batik of Subang by direct selling, namely direct promotion via online media in the form of whatsapp. However, these efforts have not been effective to promote batik typical of Subang, especially in terms of coverage of promotional targets.